Leveraging the satellite-based climate data record CLARA-A3 to understand the climatic trend regimes relevant for solar energy applications over Europe - A. Devasthale; S. Andersson; E. Engström; F. Kaspar; J. Trentmann; A. Duguay-Tetzlaff; J. F. Meirink; E. Kjellström; E. Kjellström; T. Landelius; M. A. Thomas; K.-G. Karlsson (Earth System Dynamics)
Efficient transitioning to renewable energy requires a fundamental understanding of the past and future climate change. This is particularly true in the case of solar energy, since the surface incoming solar radiation (SIS) is heavily regulated by atmospheric essential climate variables (ECVs) such as aerosols and clouds. Given the complexity of the interactions and feedbacks in the Earth system, even small changes in ECVs could have large direct and indirect effects on SIS. The net efficacy of the solar energy systems designed therefore depends on how well we account for the role of ECVs in modulating SIS. In this study, by leveraging the satellite-based climate data record (CDR) CLARA-A3, we investigate the recent trends in SIS and cloud properties over Europe during the 1982–2020 period. Furthermore, we derive emerging climatic trend regimes that are relevant for solar energy applications. Results show a large-scale increase in SIS in spring and early summer over Europe, particularly noticeable in April and June. The corresponding trends in cloud fraction and cloud optical thickness and their correlation with SIS suggest an increasingly important role of clouds in defining the favourable and unfavourable conditions for solar energy applications. We also note a strong spatiotemporal variability in trends and correlations. The results provide valuable metrics for the evaluation of climate models that have a dynamically integrated solar energy component.